Measuring quality of maternity care. Issue 8 (November 2015) - Collins, Katherine J.; Draycott, Timothy
Abstract : Health-care organisations are required to monitor and measure the quality of their maternity services, but measuring quality is complex, and no universal consensus exists on how best to measure it. Clinical outcomes and process measures that are important to stakeholders should be measured, ideally in standardised sets for benchmarking. Furthermore, a holistic interpretation of quality should also reflect patient experience, ideally integrated with outcome and process measures, into a balanced suite of quality indicators. Dashboards enable reporting of trends in adverse outcomes to stakeholders, staff and patients, and they facilitate targeted quality improvement initiatives. The value of such dashboards is dependent upon high-quality, routinely collected data, subject to robust statistical analysis. Moving forward, we could and should collect a standard, relevant set of quality indicators, from routinely collected data, and present these in a manner that facilitates ongoing quality improvement, both locally and at regional/national levels. Highlights: Quality care includes patient satisfaction, best outcomes and fewest interventions. Clinical outcomes and patient experience should be prioritized over process measures. A standardised set of QIs should be produced from routinely collected data.